Approximately Quintic and Sextic Mappings Form r-Divisible Groups into Ŝerstnev Probabilistic Banach Spaces: Fixed Point Method - M. Eshaghi Gordji; Y. J. Cho; M. B. Ghaemi; H. Majani (Discrete Dynamics in Nature and Society)
Using the fixed point method, we investigate the stability of the systems of quadratic-cubic and additive-quadratic-cubic functional equations with constant coefficients form r-divisible groups into Ŝerstnev probabilistic Banach spaces.